Agama Sebagai Institusi Sosial (Tinjauan Literatur Sosiologi Agama) - Sahdin Hasibuan; Muhammad Fikih Alpiansyah; Dermawan Jihad; Fahrul Rozi; Ahmad Ammar (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2025)
This study aims to explore the role of religion as a social institution in the context of the study of religious sociology literature. The research methodology applied in this study is qualitative, with an approach based on literature review. The findings of the study indicate that religion functions as a social phenomenon that is inseparable from people's lives, regardless of any level of culture. Religion will continue to maintain its existence in society, because of its fundamental function. Religion can be considered a social institution, considering its existence in society, where religion is an entity that is recognized, understood, obeyed, and respected by the community. The conflicts or tensions that arise due to religion are not caused by religion itself, but by the excessive fanaticism of its adherents or by the extreme changes that occur in their communities.